Applied study of Ahmadi Nodhi culture by Nobahar Khani and Nasabal Sabian Farahi - Miri, Osama (Sulaimani Journal for Humanities, 2024)
The culture of Hamadi is one of the most beautiful things in the world. I am a childhood cultural book for a poet who is translated and an Arabic writer for the Khans of Kurdistan. I am one of the first intellectuals who was once a Kurdish Surani Noosrao and Leo Katao. Peshaki to Peshaki to Khanakani Cordida Doctor. Because of the division of poetic culture into two cultures, the spring and the lineage of the linguists and others. Thanks to the inspiration and development of Hamadi's two cultural and cultural innovations, he offered a worthy service to the community. With the exception of Shawaz and Hamadi's cultural form, it is difficult to understand the two poetic cultures of the past. Thank you for your biological and spiritual contribution to Sheikh Nawabang and the Qutabian's contribution to the culture of the Kurdish language. The household of the Kurdistanda is destroyed. Nisab al-Sabian, everyone who repented of the new Iranians and worked for the newly born people, gave birth to the new Kurdish people. Baykh. The heroes of Nabahar Khani, who gave the lineage of the Lasabians, gave the price of paper to the children. A few of the Khazans and a few of them were offered to the Canadian household.
Keywords: Ahmadi culture; Nobahar; Nasab alSabian; Nodehi; comparative studies